Stomach in a parastomal hernia: a rare complication of stomas. Issue 8 (18th August 2020) - Ekowo, Onyekachi Ezekiel; Al Midani, Ammar; Abdulaal, Yasser; Boshnaq, Mohamed
Abstract : Parastomal hernia (PSH) is one of the most known complications to end colostomies. However, PSH containing the stomach is rare: not many case reports were found in literature search. This case is a 92-year-old woman who was brought in by ambulance to the accident and emergency department with vomiting, abdominal distension, palpable mass on the left side of her abdomen and with reduced stoma effluent. Her abdominal CT scan showed a PSH containing a partially incarcerated gastric hernia. Although there are only few similar cases of PSH containing the stomach reported in the literature, an almost similar pattern in presentation of this unique case can be deduced following a thorough comparison of cases in the literature, which can be quite helpful both academically and clinically: they are often advanced in age and are usually women with end colostomies.